Field reports, Iowa Bird Life, summer 1995, Lee Schoenewe - Schoenewe, Lee A.et al (1995)
An annotated list of birds sighted by Lee Schoenewe. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of summer 1995. Epson - sheet feed/flatbed